Carbon nanotube growth on piezoelectric AlN films: influence of catalyst underlayers. Issue 98 (23rd October 2015) - Mirea, T.; Olivares, J.; Clement, M.; DeMiguel-Ramos, M.; de Frutos, J.; Sangrador, J.; Iborra, E.
<x xml:space="preserve">Abstract</x> Integration of carbon nanotube (CNT) forests in acoustic wave resonators has appeared interesting for sensing applications. High quality CNTs can be grown on piezoelectric AlN by using a stabilising layer for catalyst nanoparticles.